Effect of Serum Triglycerides on Clinical Outcomes in Acute Pancreatitis: Findings From a Regional Integrated Health Care System. Issue 7 (August 2017) - Sue, Laura Y.; Batech, Michael; Yadav, Dhiraj; Pandol, Stephen J.; Blumentals, William A.; von Krusenstiern, Lenore Soodak; Chen, Wansu; Wu, Bechien U.
Abstract : Objectives: The aim of this study was to evaluate the effect of serum triglycerides on the development of multiple or persistent organ failure in patients with acute pancreatitis. Methods: A retrospective cohort study was conducted among patients hospitalized for acute pancreatitis between 2006 and 2013. Triglyceride levels measured before and within 72 hours of admission were compared. In addition, the effect of triglyceride levels on the development of multiple or persistent organ failure during hospitalization for acute pancreatitis was assessed. Results: Among 2519 patients, 267 patients (10.6%) developed organ failure, of which 75 patients developed multiple system organ failure and 82 patients developed persistent organ failure. Triglyceride levels in patients who developed organ failure were initially much higher than in patients who did not develop organ failure, but by 72 hours into admission, approached levels of patients who did not develop organ failure. Approximately 8% of patients had triglyceride levels greater than 500 mg/dL, the majority of which had similarly high levels before admission. Conclusions: Increased triglyceride levels were associated with the development of multiple or persistent organ failure among patients hospitalized with acute pancreatitis. Patients with high triglyceride levels at the time of admission were likely to have high triglyceride levels before admission. Abstract : Supplemental digital content is available in the text.